The philosophy of John Norris - Mander, W. J. (Oxford : Oxford University Press, 2008)
W.J. Mander presents this study of the English philosopher/theologian John Norris (1657-1711). Best known as a critic of John Locke, Norris incorporated ideas of Augustine Malebranche, Plato, the Cambridge Platonists, and the scholastics into an original synthesis, highly influential in his day.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Norris, John, -- 1657-1711.